Determinants of poverty in opposite two locations, usaquén y ciudad bolívar, bogotá colombia (2013)
In summary set out below a comparison of poverty levels in the towns of Usaquén and Ciudad Bolivar, its most important characteristics and limitations, which are observed under measurement methods such as the Unsatisfied Basic Needs (UBN), Quality Index of life (ICV) and inequality indices, all based on social and economic indicators Amartya Sen's theories about the welfare of the individual. As locations are studied by using these parameters to show the overall situation in terms of quality health, education, employment and other determinants, which will identify the factors that characterize them. Given the above analysis is generated to guide the development of social policies in local development, emphasizing the development of strategic and flexible programs that are of great impact and produce a real solution in addressing poverty, so attacking efficiently this problem that profoundly affects the social fabric at the collective and individual.